Topographic anatomy of the subthalamic nucleus localized by high-resolution human brain atlas superimposing digital images of cross-sectioned surfaces and histological images of microscopic sections from frozen cadaveric brains. (July 2018) - Kawasaki, Takashi; Shin, Masahiro; Kimura, Yuiko; Umitsu, Yoshitomo; Matsumura, George; Yokochi, Fusako; Okiyama, Ryoichi; Taniguchi, Makoto; Arai, Nobutaka
Highlights: We created a new brain atlas from cadaveric brains with serial frozen sections. The borders of nucleus on DICSS corresponded to the histological borders on DIMS. The coordinates of the central point of STN were calculated from 3DR models of STN. We have used this atlas for assessment of electrode positions after DBS surgery. Abstract: Despite the recent advent of neuro-radiographic techniques, creating a 'perfect' human brain atlas providing precise and consistent images with minimal distortion is practically difficult. In this study, we created a new human brain atlas from cadaveric brains with serial sections of 50 μm thickness covering the entire basal ganglia. Human cerebral hemispheres were obtained from 10 donated cadavers and fixed in 10% formalin solution, cut in a block measuring 50 mm × 30 mm × 50 mm around the midpoint of the anterior and posterior commissures and frozen at −40 °C. Each block was cut into 50-μm-thick sections on the freezing microtome and the cross-sectioned surface was photographed. Simultaneously, every 10th slice from one sagittal hemisphere was sampled and stained using the Kluver-Barrera method. Prepared slides were photographed under light microscopy, and data from digital images of the cross-sectioned surface (DICSS) and digital images from microscopic sections (DIMS) were processed. Gray areas on DICSS largely represented areas of dense cellularity, and around subthalamic nucleus (STN), the zona incerta and field of Forel were clearly distinguishable on the anterosuperior side, as was the substantia nigra on the caudal side. DICSS successfully delineated the anatomical structure identical to the STN and surrounding contiguous nuclei. This new brain atlas will allow elucidation of anatomy that cannot be clearly disclosed from modern radiographic imaging or is very difficult to analyze with spatially inconsistent histological sections, and will contribute to further progress in anatomical studies of the human basal ganglia.